Doing Bioethics in the Philippines: Philippine Bioethics and the Challenge of Cross-Cultural Medicine - Sy, Peter (Silliman Journal, 2022)
The intent of this paper is to briefly outline three major concerns: the culture of bioethics as it bears on the thematization of health and illness in the Philippines; the challenge that Filipino traditional medical views pose on bioethical discourse; and the prospects of doing bioethics in the country. Limited in space and scope, the discussion restricts Thioethics" to include only philosophical-ethical as well as cultural concerns related to medicine. Issues attendant on other spheres of "bios," like the environment, are excluded. At the core of this pa-per is the importance of understanding the differences in medical and philosophical categories used by biomedicine and Filipino tra-ditional medicine. Recognition of the medical or philosophical-ethical gap between the two medical traditions is crucial in the at-tempt to forge workable paradigms for a genuine cultural dialogue in the Philippines.